A necessity of establishing the law for oneself - Khizanishvili, S.; Taliashvili , A. (Advances in Social Sciences Research Journal, 2021)
In the information age, social development trends clearly show that a person endowed with technical intelligence is somehow alienated from his own existence and is spiritually empty and "kinless". In this paper, we focus on this most difficult problem. The pathos of our discussion is as follows: understanding and sharing the difficulties of existence is the most reliable and unmistakable way of human self-knowledge and self-exaltation. In any historical section, a legal entity including an individual, nation, country, or world community, is obliged to verify the veracity of this path. Especially we need it from the perspective of our troubled but at the same time "successful century". It is obvious fact that in the twenty-first century, in the age of technical civilization, humanity fights to save human lives - in an unusual and unexpectedly difficult situation caused by COVID-19. A few years ago, we could never ever imagine that the world would "stop". We would believe that noisy traffic between states would stop, movement within countries would slow down, people would be forced to stay at home, meetings with each other would become dangerous, and due to lack of vaccine, millions of people would die. What are we dealing with? How can we overcome the most difficult challenges caused by co-existence with COVID? How do we evaluate what’s going on? It is difficult, extremely difficult to answer these questions, but the most difficult conditions are forcing us to find reasonable answers to such questions.